Ancora sulla dialettica testo-testimone: il «Libro di sentenze», e i detti dei filosofi, nel manoscritto Siena BC I VI 5 (= S2) (Carte Romanze, 2024)
On the one hand, the paper investigates the contents of a vast and garbled section of the multi-text MS Siena BC I VI 5. On the other hand, it focuses on one of the texts in that section, the Libro di sentenze, by way of comparing it with the rest of the manuscript tradition, consisting of a total of five witnesses. Given the variability of the presence of the witnesses for each paragraph, even the operation of approaching the archetype which is possible through textual criticism leads to a fragmented reconstruction that varies throughout the text.
Keywords: Libro di sentenze; textual transmission; multi-text manuscripts